Relationship among pain, function, and motor activity in early hemiplegic patients - Talu, Burcu; Kamışlı, Suat; Talu, Yasin (İnönü Üniversitesi Tıp Fakültesi, 2018)
Aim: Evaluation of the relationship among upper extremity pain, function, and motor activity in early hemiplegic patientsMaterial and Methods: Fifty-three subjects, who had suffered hemiplegia between 1-3 months after stroke, were included in this study. Visual Analogue Scale was used for pain assessment, Fugl-Meyer Upper Extremity Motor Assessment Scale was used for upper extremity function evaluation, and Motor Activity Log-28 was used for evaluating motor activity after the demographic data of the subjects were recorded. Brunnstrom stages were used to identify, define, and quantify the recovery stages after stroke.Results: The average age of the individuals participating in the study was 54.56±8.10, and the Body Mass Index was 26.12±3.68. The subjects’ rest pain score was 30.00±19.90 and the activity pain score 42.83±24.44. The total score of the Fugl-Meyer UpperExtremity Motor Evaluatıon Scale was 18.84±17.08, the Quality of Movement sub-parameter score of the Motor Activity Log was 28 0.89±0.87, and the Amount of Use sub parameter score was 0.93±0.92. The relationship between the upper extremity function of the patients and motor activity was observed, which showed that all sub-parameters had a moderate correlation in the positive direction (r=0.539-0.779, p<0.001). However, there was no relationship between pain, function and motor activity (r=0.054-0.238,p=0.086-0.700).Conclusion: This study showed that upper extremity motor activity and function were significantly affected and closely related to each other in early hemiplegic patients. However, there was no correlation between pain, function and motor activity.
Keywords: hemipleji